Efficacy of Photobiomodulation Therapy for Orthodontic Pain Control Following the Placement of Elastomeric Separators: A Randomized Clinical Trial - Mirhashemi, Amirhossein; Rasooli, Reza; Shahi, Shiva; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2021)
Introduction: Controlling pain in orthodontic patients has gained special attention. This study assessed the efficacy of photobiomodulation therapy (PBMT) for pain control following the placement of elastomeric separators. Methods: This split-mouth single-blind randomized clinical trial evaluated 30 orthodontic patients who required posterior elastomeric separators. The two maxillary quadrants were randomized into the laser and control groups. In the laser quadrant, an 808 nm diode laser (400 mW, 15.60 J/cm2,11 seconds, continuous-wave, contact mode) was irradiated to the cervical third of the maxillary first molar roots 24 hours prior to the placement of separators. The control quadrant received placebo radiation by a light-curing unit. The patients received the second laser cycle right before the placement of separators 24 hours later. The level of self-perceived pain was recorded at 0, 2, 6, 24, and 72 hours and 5 days after the intervention in the laser and control quadrants using a visual analog scale (VAS). Data were analyzed using the analysis of variance (ANOVA) and paired-samples t-test. Results: The trend of change in the pain score was similar in both groups. The pain score was significantly lower in the laser group than the control group at all-time points (P<0.05) except at time 0. The pain score increased in the first 6 hours and reached its maximum level in 24 hours in both groups. Conclusion: PBMT by an 808 nm diode laser can effectively decrease pain following the placement of elastomeric separators DOI:10.34172/jlms.2021.08